A nickel-based catalyst and its preparation method and application
By using perovskite oxide LaMn0.3Al0.7O3 as a support in nickel-based catalyst and adjusting the pH value of the precursor, the problem of insufficient low-temperature activity of nickel-based catalysts is solved, and efficient ammonia decomposition reaction is achieved, which improves the The stability and ammonia decomposition efficiency of the catalyst are suitable for industrial applications.
Patent Information
- Application Number
- CN202310330501.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-03-31
AI Technical Summary
The nickel-based catalyst has insufficient low temperature activity in ammonia decomposition reaction, resulting in low ammonia decomposition efficiency and insufficient stability, which limits its development in industrial applications.
The perovskite oxide LaMn0.3Al0.7O3 was used as the support, and the Ni/LaMn0.3Al0.7O3 catalyst was prepared by adjusting the pH value of the precursor to enhance the interaction between nickel and the support and improve the activity and stability of the catalyst.
It significantly improves the low-temperature ammonia decomposition activity and stability of the catalyst, improves the ammonia decomposition efficiency, and has a simple process and low cost, making it suitable for large-scale industrial applications.
Smart Images

Figure CN116408103B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nickel-based catalyst and a preparation method thereof and application thereof in ammonia decomposition reaction, belonging to the technical field of catalytic materials. Background Art
[0002] The extensive use of fossil fuels is the main cause of energy shortage and environmental pollution. It is urgent to find clean new energy. Hydrogen has a high calorific value (142 MJ·kg -1 ), clean, and diverse application scenarios, it has become the focus of research on new energy. However, the difficulties in hydrogen storage and transportation and poor safety have restricted the development of the hydrogen energy industry. In order to solve this problem, it is particularly important to develop safe and efficient hydrogen storage materials and in-situ hydrogen production technology.
[0003] Compared with carbon-containing hydrogen storage carriers such as methane and methanol, ammonia is a good carrier with the following advantages: (1) It has a higher volume energy density (108 kg-H2 / m 3 NH3) and hydrogen content (17.6 wt%). (2) Easy to liquefy and transport (3) The product is safe and contains no CO x (4) The technology of synthetic ammonia is mature, which greatly reduces the cost of ammonia. Using ammonia as a hydrogen storage medium to produce hydrogen in situ through ammonia decomposition reaction is expected to solve the problems of H2 as a direct energy source in storage, transportation, safety, cleanliness, cost, etc. The key is to develop a low-temperature and high-efficiency catalyst.
[0004] At present, ammonia decomposition catalysts mainly use transition metals such as Ru, Ni, Fe, Co, Mo and alloys as active components. Ru stands out among many catalysts for its excellent performance at low temperatures, but its high cost and scarcity have largely limited the development of Ru catalysts in industry. Patent CN113332987A discloses a fin-shaped Ni-based ammonia decomposition hydrogen production catalyst, which has a large specific surface area and can provide more active sites for NH3. The active metal particles are evenly distributed, effectively improving the catalyst activity. Patent CN113198476A introduces a transition metal-doped modified carrier γ-Al2O3 loaded Ni ammonia decomposition catalyst; through the doping modification of Co, Fe and Cu, the Ni / γ-Al2O3 catalyst generates smaller and more evenly dispersed active species, effectively reducing the activation energy required for the reaction and thus improving the ammonia decomposition efficiency. When the Co doping amount is 5 wt%, the catalyst activity can reach 99% at 700°C.
[0005] In summary, although Ni catalysts have many advantages such as high activity and low price, problems such as low low-temperature activity, easy sintering, and insufficient stability still need to be solved. The efficiency of ammonia decomposition catalysts is closely related to the interaction between active metals and carriers. Common carriers include Al2O3, MgO, ZrO2, SiO2, CeO2, activated carbon and carbon nanotubes, etc. The performance of Ni catalysts prepared by using these carriers is not ideal. The present invention selects perovskite materials as carriers, and changes the physical properties of the carriers by adjusting the acid-base environment of the precursors, thereby enhancing the interaction between the metals and the carriers, thereby improving the catalytic performance of the catalysts. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the insufficient low-temperature activity of nickel-based catalysts in ammonia decomposition catalysts, and to provide an ammonia decomposition catalyst with high low-temperature ammonia decomposition activity and a preparation method thereof. 0.3 Al 0.7 O3 catalyst adjusts the pH value of the precursor by ammonia water, which enhances the interaction between the carrier and the active component and increases the number of basic sites on the carrier, thereby improving the ammonia decomposition efficiency.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A nickel-based catalyst, the nickel-based catalyst is composed of active metal nickel and perovskite-type oxide LaMn 0.3 Al 0.7 O3 carrier composition; among them, active metal nickel accounts for 5-10 wt%, carrier LaMn 0.3 Al 0.7 O3 accounts for 90-95 wt%, and the sum of the two mass percentages is 100%.
[0009] A method for preparing a nickel-based catalyst comprises the following steps:
[0010] (1) Weigh lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, and citric acid, add deionized water to dissolve, add ethylene glycol, and adjust the pH value. Heat and stir in a 90 °C oil bath until it becomes a gel. Then transfer to an oven and dry at 140 °C for 12 h to obtain a precursor.
[0011] (2) Grind the precursor into powder and calcine it in a muffle furnace to obtain LaMn 0.3 Al 0.7 O3 carrier.
[0012] (3) Using nickel nitrate solution as the impregnation solution, impregnate the LaMn obtained in the previous step 0.3 Al 0.7 The O3 carrier is dried and calcined at 120°C to obtain the nickel-based catalyst.
[0013] Furthermore, in step (1), lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate and citric acid are weighed in a ratio of La: (Mn + Al): citric acid of 1: 1: (1.5-3.0); the molar ratio of total metal elements La + Mn + Al: ethylene glycol is 1: (1.5-3.0).
[0014] Furthermore, the reagent used for adjusting the pH value in step (1) is ammonia water, and the pH value adjustment range is 1-11, preferably 5-10.
[0015] Furthermore, the precursor in step (2) is calcined at a temperature of 600-900°C for a calcination time of 1-7 h. The loaded nickel sample in step (3) is calcined at a temperature of 200-450°C for a calcination time of 2-4 h.
[0016] Application: The nickel-based catalyst is used in the low-temperature ammonia decomposition reaction to produce hydrogen, with the decomposition temperature being 300-800°C.
[0017] The technical solution of the present invention has the following characteristics and advantages:
[0018] The present invention uses non-precious metal nickel as the active component and LaMn 0.3 Al 0.7 O3 perovskite is used as a carrier. By adjusting the acidity and alkalinity of the precursor, the specific surface area of the carrier is increased and the dispersion of the active component nickel is improved. At the same time, the surface of the carrier has more alkaline sites, which greatly improves the low-temperature ammonia decomposition activity of the catalyst.
[0019] The doping of Al ions at the B site changes the coordination between the original La-Mn bonds, causing the original octahedral structure to be distorted, which is conducive to the generation of carrier defects and enhances the electronic transport performance of the carrier. In addition, Al 3+ The strong interaction with Ni can effectively protect Ni from sintering and growth during the reaction, thereby improving the activity and stability of the catalyst. Using ammonia as the alkaline solution to adjust the pH of the system has the following advantages: First, ammonia acts as a complexing agent in the metal solution to promote the perovskite LaMn 0.3 Al 0.7 The formation of O3; secondly, no impurity ions are introduced during the adjustment of ammonia water, and NH4 can be effectively removed by subsequent heating and roasting. + The introduction of ammonia water enhances the interaction between the active component and the carrier, and the catalyst has more basic sites, thereby increasing the efficiency of ammonia decomposition. 0.3 Al 0.7 O3 catalyst has the advantages of simple preparation, stability and high efficiency, low cost and easy use in large-scale hydrogen production. It is an excellent ammonia decomposition catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the ammonia decomposition activity diagram of the catalysts of Examples 1, 2, 3 of the present invention and Comparative Example 1.
[0021] Figure 2 The XRD spectra of the samples prepared in the embodiments and comparative examples of the present invention are shown in FIG. Figure 2 It can be seen that the diffraction peak shifts to a smaller angle, indicating that Al is successfully incorporated into the B site.
[0022] Figure 3 H2-TPR diagrams of samples prepared in the embodiments of the present invention and the comparative examples are shown in FIG. Figure 3 It can be seen that compared with Comparative Example 1, the temperatures of the reduction peaks of Examples 1, 2, and 3 all move toward high temperatures, among which Example 1 has the highest reduction temperature, indicating that the interaction between the active component and the carrier is correspondingly enhanced. When the pH value is in the range of 5-10, the interaction between the active component and the catalyst carrier is stronger.
[0023] Figure 4 The CO2-TPD diagram of the samples prepared in the embodiments of the present invention and the comparative examples shows that when the pH value is adjusted in the range of 5-10, the catalyst has more alkaline sites, which is beneficial to the ammonia decomposition reaction, thereby improving the activity. DETAILED DESCRIPTION
[0024] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0025] Example 1
[0026] 5 wt% Ni / LaMn 0.3 Al 0.7 O3-5 Catalyst
[0027] (1) LaMn 0.3 Al 0.7Preparation of O3-5 carrier: Adjust the pH of the precursor to 5. Take 10 mmol of the carrier as an example to calculate the mass of each component raw material. ① Weigh 4.3310 g La(NO3)3·6H2O, 0.7530 g Mn(NO3)2·4H2O, 2.6259 g Al(NO3)3·9H2O, 2.8820 g citric acid and 1672 μL ethylene glycol, add 50 mL deionized water to dissolve, place on a magnetic stirrer, and use a pH meter to measure the pH value of the solution in real time, and add ammonia solution drop by drop to adjust the pH value to 5. Then heat and stir in a 90 °C oil bath until it is gel-like, then transfer to a 140 °C oven and dry for 12 h to obtain the precursor. ② The precursor was ground into powder and calcined in a muffle furnace. The temperature was raised from room temperature to 400 °C at a rate of 2 °C / min and maintained for 30 min. Then the temperature was raised to 900 °C at a rate of 2 °C / min and maintained for 7 h. Finally, the temperature was lowered to obtain LaMn 0.3 Al 0.7 O3-5 carrier.
[0028] (2) Preparation of catalyst by traditional impregnation method: nickel nitrate solution was used as the impregnation solution, and the impregnation product was dried and calcined in a muffle furnace at a heating rate of 1 °C / min from room temperature to 300 °C and maintained for 2 h, and then heated to 450 °C at a rate of 2 °C / min and maintained for 2 h.
[0029] (3) Catalyst screening and tableting: The catalyst powder obtained in step (2) was tableted, and then ground and crushed into a 60-80 mesh standard sieve to finally obtain a 5 wt% Ni / LaMn catalyst with a particle size of 60-80 mesh. 0.3 Al 0.7 O3-5 catalyst particles.
[0030] (4) Activity evaluation: 0.1 g of the catalyst obtained in step (3) was placed in a quartz tube and reduced at 500 °C in a 50% H2-Ar atmosphere for 3 h, followed by purging under an Ar atmosphere for 1 hour. Finally, the activity was evaluated at 450-700 °C, with an NH3 flow rate of 50 mL / min.
[0031] Example 2
[0032] 5 wt% Ni / LaMn 0.3 Al 0.7 O3-8 Catalyst
[0033] (1) LaMn 0.3 Al 0.7Preparation of O3-8 carrier: Adjust the pH of the precursor to 8. Take 10 mmol of the carrier as an example to calculate the mass of each component raw material. ① Weigh 4.3310 g La(NO3)3·6H2O, 0.7530 g Mn(NO3)2·4H2O, 2.6259 g Al(NO3)3·9H2O, 2.8820 g citric acid and 1672 μL ethylene glycol, add 50 mL deionized water to dissolve, place on a magnetic stirrer, and use a pH meter to measure the pH value of the solution in real time, and add ammonia solution drop by drop to adjust the pH value to 8. Then heat and stir in a 90 °C oil bath until it is gel-like, then transfer to a 140 °C oven and dry for 12 h to obtain the precursor. ② The precursor was ground into powder and calcined in a muffle furnace. The temperature was raised from room temperature to 400 °C at a rate of 2 °C / min and maintained for 30 min. Then the temperature was raised to 900 °C at a rate of 2 °C / min and maintained for 7 h. Finally, the temperature was lowered to obtain LaMn 0.3 Al 0.7 O3-8 carrier.
[0034] (2) Preparation of catalyst by traditional impregnation method: nickel nitrate solution was used as the impregnation solution, and the impregnation product was dried and calcined in a muffle furnace at a heating rate of 1 °C / min from room temperature to 300 °C and maintained for 2 h, and then heated to 450 °C at a rate of 2 °C / min and maintained for 2 h.
[0035] (3) Catalyst screening and tableting: The catalyst powder obtained in step (2) was tableted, and then ground and crushed into a 60-80 mesh standard sieve to finally obtain a 5 wt% Ni / LaMn catalyst with a particle size of 60-80 mesh. 0.3 Al 0.7 O3-8 catalyst particles.
[0036] (4) Activity evaluation: 0.1 g of the catalyst obtained in step (3) was placed in a quartz tube and reduced at 500 °C in a 50% H2-Ar atmosphere for 3 h, followed by purging under an Ar atmosphere for 1 hour. Finally, the activity was evaluated at 450-700 °C, with an NH3 flow rate of 50 mL / min.
[0037] Example 3
[0038] 5 wt% Ni / LaMn 0.3 Al 0.7 O3-10 Catalyst
[0039] (1) LaMn 0.3 Al 0.7Preparation of O3-10 carrier: Adjust the pH of the precursor to 10. Take 10 mmol of the carrier as an example to calculate the mass of each component raw material. ① Weigh 4.3310 g La(NO3)3·6H2O, 0.7530 g Mn(NO3)2·4H2O, 2.6259 g Al(NO3)3·9H2O, 2.8820 g citric acid and 1672 μL ethylene glycol, add 50 mL deionized water to dissolve, place on a magnetic stirrer, and use a pH meter to measure the pH value of the solution in real time, and add ammonia solution drop by drop to adjust the pH value to 10. Then heat and stir in a 90 °C oil bath until it is gel-like, then transfer to a 140 °C oven and dry for 12 h to obtain the precursor. ② The precursor was ground into powder and calcined in a muffle furnace. The temperature was raised from room temperature to 400 °C at a rate of 2 °C / min and maintained for 30 min. Then the temperature was raised to 900 °C at a rate of 2 °C / min and maintained for 7 h. Finally, the temperature was lowered to obtain LaMn 0.3 Al 0.7 O3-10 carrier.
[0040] (2) Preparation of catalyst by traditional impregnation method: nickel nitrate solution was used as the impregnation solution, and the impregnation product was dried and calcined in a muffle furnace at a heating rate of 1 °C / min from room temperature to 300 °C and maintained for 2 h, and then heated to 450 °C at a rate of 2 °C / min and maintained for 2 h.
[0041] (3) Catalyst screening and tableting: The catalyst powder obtained in step (2) was tableted, and then ground and crushed into a 60-80 mesh standard sieve to finally obtain a 5 wt% Ni / LaMn catalyst with a particle size of 60-80 mesh. 0.3 Al 0.7 O3-10 catalyst particles.
[0042] (4) Activity evaluation: 0.1 g of the catalyst obtained in step (3) was placed in a quartz tube and reduced at 500 °C in a 50% H2-Ar atmosphere for 3 h, followed by purging under an Ar atmosphere for 1 hour. Finally, the activity was evaluated at 450-700 °C, with an NH3 flow rate of 50 mL / min.
[0043] In order to further illustrate the effect of the acid-base environment of the precursor on LaMn 0.3 Al 0.7 The influence of O3 catalyst carrier is important in the present invention. LaMn without adding ammonia to adjust pH value is selected. 0.3 Al 0.7 The O3 catalyst was used as comparative example 1 for comparison.
[0044] Comparative Example 1
[0045] 5 wt% Ni / LaMn 0.3Al 0.7 O3 Catalyst
[0046] (1) LaMn 0.3 Al 0.7 Preparation of O3 carrier: No ammonia water is added. The following is an example of 10 mmol of carrier to calculate the mass of each component raw material. ① Weigh 4.3310 g La(NO3)3·6H2O, 0.7530 g Mn(NO3)2·4H2O, 2.6259 g Al(NO3)3·9H2O, 2.8820 g citric acid and 1672μL ethylene glycol, add 50mL deionized water to dissolve, and place on a magnetic stirrer. At this time, no ammonia water is added. The pH value of the system is 1.0. Then heat and stir in a 90 ℃ oil bath until it is gel-like, then transfer to a 140 ℃ oven and dry for 12 h to obtain a precursor. ② Grind the precursor and place it in a muffle furnace for calcination. The heating rate is 2 ℃ / min from room temperature to 400 ℃ and maintained for 30 min, then increase the temperature to 900 ℃ at 2 ℃ / min and maintain for 7 h, and finally cool down to obtain LaMn 0.3 Al 0.7 O3 carrier.
[0047] (2) Preparation of catalyst by traditional impregnation method: nickel nitrate solution was used as the impregnation solution, and the impregnation product was dried and calcined in a muffle furnace at a heating rate of 1 °C / min from room temperature to 300 °C and maintained for 2 h, and then heated to 450 °C at a rate of 2 °C / min and maintained for 2 h.
[0048] (3) Catalyst screening and tableting: The catalyst powder obtained in step (2) was tableted, and then ground and crushed into a 60-80 mesh standard sieve to finally obtain a 5 wt% Ni / LaMn catalyst with a particle size of 60-80 mesh. 0.3 Al 0.7 O3 catalyst particles.
[0049] (4) Activity evaluation: 0.1 g of the catalyst obtained in step (3) was placed in a quartz tube and reduced at 500 °C in a 50% H2-Ar atmosphere for 3 h, followed by purging under an Ar atmosphere for 1 hour. Finally, the activity was evaluated at 450-700 °C, with an NH3 flow rate of 50 mL / min.
[0050] Table 1 shows the ammonia decomposition activity data of the catalysts of Examples 1, 2, 3 and Comparative Example 1 of the present invention.
[0051] In summary, by adjusting the pH value of the precursor in the range of 5-10, Ni / LaMn 0.3 Al 0.7The activity of the O3 catalyst is greatly improved. Compared with the comparative example 1 in which the pH of the precursor is not adjusted, the ammonia decomposition efficiency of the adjusted examples 1, 2, and 3 is improved to varying degrees, among which example 1 has the best ammonia decomposition efficiency, and the efficiency is significantly improved by 20% at 600 ° C. The results show that the adjustment of the precursor pH can effectively enhance the ammonia decomposition efficiency of the perovskite carrier. The reason is that the precursor is conducive to the ammonia decomposition reaction in an alkaline environment, enhances the interaction between Ni and the carrier, and greatly improves the alkaline sites on the catalyst, thereby accelerating the ammonia decomposition reaction. Therefore, the catalyst prepared by this invention has a simple process, is economical and efficient, and has a good application prospect in ammonia decomposition and hydrogen production.
[0052] Table 1 Ammonia decomposition activity of catalysts in Examples and Comparative Examples (%)
[0053]
[0054] The above description is a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nickel-based catalyst for hydrogen production by decomposing ammonia, characterized in that: The nickel-based catalyst is composed of active metal nickel and perovskite-type oxide LaMn 0.3 Al 0.7 O3 carrier composition; among them, active metal nickel accounts for 5-10 wt%, carrier LaMn 0.3 Al 0.7 O3 accounts for 90-95 wt%, and the sum of the two mass percentages is 100%; The method for preparing the nickel-based catalyst comprises the following steps: (1) Weigh lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, and citric acid, add deionized water to dissolve, add ethylene glycol, and adjust the pH value to 5-10 with ammonia water, heat and stir in a 90 ° C oil bath until it becomes a gel, then transfer to an oven and dry at 140 ° C for 12 h to obtain a precursor; (2) Grind the precursor into powder and calcine it in a muffle furnace to obtain LaMn 0.3 Al 0.7 O3 carrier; (3) Using nickel nitrate solution as the impregnation solution, the LaMn obtained in step (2) is impregnated 0.3 Al 0.7 The O3 carrier is dried and calcined at 120°C to obtain the nickel-based catalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), lanthanum nitrate hexahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate and citric acid are weighed in a ratio of La: (Mn + Al): citric acid of 1: 1: (1.5-3.0); the molar ratio of total metal elements: ethylene glycol is 1: (1.5-3.0).
3. The preparation method according to claim 1, characterized in that: The calcination temperature in step (2) is 600-900°C and the calcination time is 1-7 h.
4. The preparation method according to claim 1, characterized in that: The calcination temperature in step (3) is 200-450°C and the calcination time is 2-4 h.
5. Use of the nickel-based catalyst obtained by the method according to claim 1 in the reaction of decomposing ammonia to produce hydrogen, characterized in that: The decomposition temperature of ammonia is 300-800 ℃.